Comparative Physiological and Transcriptome Profiles Uncover Salt Tolerance Mechanisms in Alfalfa - Li, Jiali; Ma, Maosen; Sun, Yanmei; Lu, Ping; Shi, Haifan; Guo, Zhenfei; Zhu, Haifeng (Frontiers in Plant Science, 2022)
Salinity is a major limiting factor that affects crop production. Understanding of the mechanisms of plant salt tolerance is critical for improving crop yield on saline land. Alfalfa (Medicago sativa L.) is the most important forage crop, while its salt tolerance mechanisms are largely unknown. The physiological and transcriptomic responses in two contrasting salt tolerant cultivars to salinity stress were investigated in the present study. ‘Magnum Salt’ showed higher salt tolerance than ‘Adrenalin’, with higher relative germination rate, survival rate, biomass and K+/Na+ ratio after salt treatment. Activities of antioxidant enzymes SOD, CAT and GR and proline concentrations were upregulated to higher levels in roots and shoots in Magnum Salt than in Adrenalin after salinity stress, except for no difference in GR activity in shoots, and lower levels of O2⋅- and H2O2 were accumulated in leaves. It was interesting to find that salinity caused a decrease in total unsaturated fatty acid in Adrenalin other than Magnum Salt, C18:2 was increased significantly after salinity in Magnum Salt, while it was unaltered in Adrenalin. High quality RNA-Seq data was obtained from samples of Magnum Salt and Adrenalin at different time points (0, 2, and 26 h). Generally, ‘phagosome’, ‘TCA cycle’ and ‘oxidative phosphorylation’ pathways were inhibited by salinity stress. Upregulated DEGs in Magnum Salt were specifically enriched in ‘fatty acid metabolism’, ‘MAPK signaling’ and ‘hormone signal transduction’ pathways. The DEGs involved in ionic homeostasis, ROS-scavenging and fatty acid metabolism could partially explain the difference in salt tolerance between two cultivars. It is suggested that salt tolerance in alfalfa is associated with regulation of ionic homeostasis, antioxidative enzymes and fatty acid metabolism at both transcriptional and physiological level.